Modification of maritime boundaries as a result of sea level rise - Holtz, Carolin Ewa (Riga Graduate School of Law, 2022)
Rising sea levels due to climate change lead to the modification of maritime state boundaries. According to the law of the seas, baselines from which maritime zones are measured are ambulatory and shift landward due to rising sea levels. However, the United Nations Convention on the Law of the Sea does not provide a legal solution to the moving boundaries. Practise and research provide several initiatives seeking to resolve this issue by fixing baselines or outer limits of maritime zones. The present work analyses the legal implications of rising sea levels under UNCLOS and possible solutions thereof on the territory of coastal and island states. After a comprehensive evaluation of international law, state practise, and academic literature, it is certain that several international and regional approaches address the challenges of the modification of maritime boundaries due to sea level rise in a suitable and reasoned matter. As a result, no unified solution for all affected states under the law of the sea exists.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Other law::International law; Law of the Sea; United Nations Convention on the Law of the Sea